Analisa Dan Perancangan Sistem Pengelompokan Data Rekam Medis Pasien Pada Puskesmas Cipayung Depok Menggunakan Metode K-Means Berbasis Web - Gulo, Anania; Anis, Muhammad (CV. Shofanah Media Berkah, 2024)
Cipayung Depok Community Health Center is an institution that provides health services for the community which was founded in 1992 on Jl.Blok Rambutan No.108 Rt 01/04 Cipayung, Depok. Cipayung Community Health Center can serve around 100 to 120 patients every day, in one month there can be up to 3,000 to 3,600 patients with symptoms of different diseases and this is what causes the community health center to have difficulty in determining appropriate counseling regarding a disease. which is caused. Complaints suffered by patients can be a reference in finding information on the correct diagnosis or prevention of a disease. Community health centers also play an important role in preventing disease in an area, this can be done through counseling, outreach and other forms of prevention. Each patient's data is also recorded, including patient complaints, personal biodata and treatment and so on. This research aims to determine the diseases that patients often complain about. In this research, data collection was carried out through observation and literature study. Grouping medical record data has succeeded in making it easier for the health center to know what diseases are often found and become complaints from patients.